Summarized datasheet for multi-omics response of three Exaiptasia strains to heat stress: a new way to process omics data - Cziesielski, Maha J. (BMC Res Notes, 2018)
OBJECTIVES: Corals, the building blocks of reef ecosystems, have been severely threatened by climate change. Coral bleaching, the loss of the coral’s endosymbiotic algae, occurs as a consequence of increasing ocean temperature. To understand mechanisms of stress tolerance in symbiotic cnidarians, the sea anemone Exaiptasia pallida from different regions was heat stressed. The three strains originated from the Red Sea, Hawaii and North Carolina, each with different temperature profiles, enabling a comparative study of local adaptation strategies. DATA DESCRIPTION: Whole transcriptome and proteome data were collected from all anemones at control and stress condition. As part of the analysis of this large, multi-omic data, we wrote a script that creates a tabular datasheet that summarized the transcriptomic and proteomic changes for every gene. It facilitates the search of individual genes, or a group of genes, their up- or downregulation during stress and whether this change in expression was statistically significant. Furthermore, it enables examining if changes in RNA correspond to those in proteins. The datasheet can be used for future comparisons, as well as search and development of biomarkers.